Assessment on the microbial status of potable/ drinking water in Dhaka city and the comparative analysis of different regions of the city on antibiotic resistance - Amin, Rahaf Bint; Nabila, Antara Ridha; Prova, Adiba Hasan; Rashid, Samia; Das, Devopria (2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2022.